Enhanced Oxidation of p-Toluidine Using Supported Zeolite Nanoparticles - Khadijah H. Alharbi; Walaa Alharbi; Sultan Alhayyani; L. Selva Roselin; Rosilda Selvin (Molecules, 2023)
Supported nanomaterials are becoming increasingly important in many industrial processes because of the need to improve both the efficiency and environmental acceptability of industrial processes. The unique properties of supported nanomaterials have attracted researchers to develop efficient catalytic materials in nanoscale. The extremely small size of the particles maximizes the surface area exposed to the reactant, allowing more reactions to occur. The environmental hazards resulting from the conventional manufacturing procedures for organic fine chemicals and intermediates by classical oxidation catalysis using mineral acids have forced chemical industries to seek less polluting processes. The present study aimed to oxidize p-toluidine by hydrogen peroxide in the presence of magnetite supported on nanocrystalline titanium silicalite-1 (M/NTS) zeolite at ambient temperature. The products detected are 4,4′-dimethylazobenzene as major product and 4,4′-dimethylazoxybenzene as minor product. Good selectivity, low cost, low wastage of materials and enhanced environmental friendliness of heterogeneous magnetite nanoparticle supported zeolite catalysts were observed. The effect of various reaction parameters such as mole ratio, catalyst weight and reusability of catalyst were studied. At the optimum reaction conditions, the oxidation activity of M/NTS catalyst was compared with M/NS catalyst, and it was found that titanium in the framework of M/NTS provided higher activity and selectivity.